2021
DOI: 10.1088/1361-6471/ac3c33
|View full text |Cite
|
Sign up to set email alerts
|

Pairing effects in nuclear pasta phase within the relativistic Thomas–Fermi formalism

Abstract: Pairing effects in non-uniform nuclear matter, surrounded by electrons, are studied in the protoneutron star early stage and in other conditions. The so-called nuclear pasta phases at sub saturation densities are solved in a Wigner-Seitz cell, within the Thomas-Fermi approximation. The solution of this problem is important for the understanding of the physics of a newly born neutron star after a supernova explosion. It is shown that the pasta phase is more stable than uniform nuclear matter on some conditions a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The results are then compared with the experimental value from the 2016 Atomic Mass Evaluation (AME2016) [105][106][107]. Since the shell effects and nucleon pairing [108] are neglected in our current study, the obtained results deviate from the experimental value, which is particularly the case for nuclei with proton/neutron numbers close to the magic numbers. In the framework of TFA, it is found that DD-LZ1 gives a better description for heavy nuclei, while the energy per baryon of light nuclei obtained with DD-ME2 are close to the experimental value.…”
Section: Resultsmentioning
confidence: 88%
“…The results are then compared with the experimental value from the 2016 Atomic Mass Evaluation (AME2016) [105][106][107]. Since the shell effects and nucleon pairing [108] are neglected in our current study, the obtained results deviate from the experimental value, which is particularly the case for nuclei with proton/neutron numbers close to the magic numbers. In the framework of TFA, it is found that DD-LZ1 gives a better description for heavy nuclei, while the energy per baryon of light nuclei obtained with DD-ME2 are close to the experimental value.…”
Section: Resultsmentioning
confidence: 88%
“…Since both the long-range attraction and short-range repulsion are incorporated in the phenomenological Gogny force and Bonn potential, the gap obtained in these calculations exhibits a non-monotonic pF-dependence. It was found [29,[41][42][43] that Δ(p F ) first increases with growing p F and then decreases with growing p F once p F exceeds roughly 0.8 fm −1 , which corresponds to ρ ≈ 0.1ρ 0 . In figure 5, we compare the p F -dependence of Δ obtained by solving the ME equations (34) and (35) with the BCS-level results obtained based on the Gogny force [29,42,43] and the Bonn potential [41] within the range of 0.2 fm −1 p F 0.8 fm −1 .…”
Section: Dyson-schwinger Equation Of Neutron Propagator Under Bare Ve...mentioning
confidence: 98%
“…It was found [29,[41][42][43] that Δ(p F ) first increases with growing p F and then decreases with growing p F once p F exceeds roughly 0.8 fm −1 , which corresponds to ρ ≈ 0.1ρ 0 . In figure 5, we compare the p F -dependence of Δ obtained by solving the ME equations (34) and (35) with the BCS-level results obtained based on the Gogny force [29,42,43] and the Bonn potential [41] within the range of 0.2 fm −1 p F 0.8 fm −1 . The Gogny result and Bonn result are quite similar to each other, but these two results are substantially different from our ME-level result.…”
Section: Dyson-schwinger Equation Of Neutron Propagator Under Bare Ve...mentioning
confidence: 98%
See 1 more Smart Citation
“…Although there exists no direct and robust observational evidence of nuclear pasta, various tantalizing observations indicate its existence [23][24][25]. Numerous theoretical attempts based on molecular dynamics simulations [22,26,27], compressible liquid-drop models [28,29], Thomas-Fermi method [6,30,31] and nuclear density functional theory [32] point towards the possibility of the pasta structures near the crust-core transition density. The amount of these structures in the inner crust plays pivotal role in the explanation of various neutron star mechanisms such as crust cooling [25,33], spin period [24], quasiperiodic oscillation in giant flares [34], transport [35], shattering of the crust [36] etc.…”
Section: Introductionmentioning
confidence: 99%